Minerality in Wine: Textual Analysis of Chablis Premier Cru Tasting Notes - Alex J. Biss; Richard H. Ellis (Australian Journal of Grape and Wine Research)
The term minerality is often used to describe high-quality still white wines produced in cooler regions, such as Chablis. What minerality means in sensory terms and what is responsible for its presence is the subject of debate, however. This study explored the concept of minerality by analysing 16,542 Chablis Premier Cru tasting notes entered into CellarTracker between 2003 and 2022 on wines three to seven years old, together with weather, topography, and soil data for the Chablis area. The top three words used to describe Chablis Premier Cru wine were citrus, minerality, and acidity. Mentions of minerality declined between 1999 and 2019 vintages, whereas those of acidity, salinity, floral, orchard fruit, and stone fruit increased. The trends for minerality and salinity were slightly stronger with the year of tasting (2005 to 2022) than vintage. Bigram analysis indicated that consumers were more than 1.5 times as likely to refer to a stony kind of minerality as a saline one and only rarely smoky minerality. Use of the term minerality was correlated with growing season temperature and sunshine hours (negatively with each), as well as vineyard aspect (negatively with percentage vineyard area facing South or South-West), but not with Kimmeridgian soil type. The results imply that soils and geology are not a principal source of minerality in Chablis wine, but growing season warmth and sunshine are relevant to minerality. There is no simple explanation of minerality in Chablis wine; however, the recent decline in the use of this term for Chablis wine may be a consequence of three factors in combination: (i) it has become less fashionable; (ii) consumers are choosing “saline” instead of “mineral” when appropriate, but retaining it for “stony” sensations; and/or (iii) warming from climate change has reduced minerality.